Children of fear: helicopter parents cultivate cluelessness - Leeuw, Lauren de (My University, 2014)
A look at the helicopter parent, the era where parents play such a significant role in their children’s lives that there is no definitive end in sight for when children will become responsible and contributing adults.
Keywords: parenting; overprotection